A silicon photomultiplier readout ASIC for time-of-flight applications using a new time-of-recovery method - Shen, Wei; Harion, Tobias; Chen, Huangshan; Briggl, Konrad; Stankova, Vera; Munwes, Yonathan; Schultz-Coulon, Hans-Christian (IEEE transactions on nuclear science, 2018)
Silicon photomultiplier timing chip (STiC) is a 64-channel mixed-mode application-specific integrated circuit in the 0.18-μm CMOS technology from Univited Microelectronics Corporation (UMC) for silicon photomultiplier (SiPM) readout with very high timing resolution. It is designed for time-of-flight measurements in positron emission tomography and high-energy physics experiments. In order to achieve the best timing performance without compromising the charge/energy measurement, a novel time-based signal processing technique called “time-of-recovery (ToR)” method has been developed and implemented in the analog front end of the chip. This technique converts the incoming charge into a digital pulse with a linearized time-overthreshold width. Measurements have shown a time jitter smaller than 20 ps for the analog front end and smaller than 40 ps for the time-to-digital converter and the digital part. A coincidence time resolution of 214-ps full-width at half-maximum (FWHM) has been obtained with STiC using 3.1×3.1×15 mm3LYSO:Ce crystals and Hamamatsu multi pixel photon counters (S12643050CN(X)). The measured energy resolution for a 511-keV photon is 11.2% FWHM after correcting for SiPM saturation effects. In this paper, we report on the details of the ToR method and how it is embedded within the STiC design; results of performance measurements as well as the 128-channel front-end module used for the EndoTOFPET-US project are also presented.
Gesehen am 02.10.2019